Characteristics of lower respiratory tract pathogens in critically ill patients with heatstroke: a retrospective multi-center study - Ma, Aijia; Jin, Xinyang; Wang, Yucong; Wang, Lietao; Shi, Lvyuan; Wan, Dingyuan; Wu, Qin; He, Min; Tang, Zhuo; Li, Jiajin; Wang, Jian; Yang, Guangwei; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
This retrospective multicenter study was conducted across 83 intensive care units (ICUs) in 16 cities in Sichuan, China. Critically ill patients diagnosed with heatstroke and lung infections were included in the study. Specimens from the lower respiratory tract were collected for microbiological testing, and the characteristics of the pathogens were described. A total of 462 patients diagnosed with heatstroke-related pulmonary infections were included, 134 patients (29.0%) tested positive for respiratory pathogens. The most frequently isolated strain was Klebsiella pneumoniae (34.3%), followed by Escherichia coli (28.4%), Staphylococcus aureus (20.9%). The results revealed that in the hyperthermic resistance group, there was a higher proportion of Pseudomonas aeruginosa [14(34.1%) vs 11(11.8%), p=0.002] and Stenotrophomonas maltophilia [4(9.8%) vs 1(1.1%), p=0.030] compared to the hyperthermic control group. And a higher proportion of Staphylococcus aureus [27(29.7%) vs 1(2.3%), p<0.001], were obtained during the earlier stages with elevated temperatures. Patients with Klebsiella pneumoniae (38.3 ± 1.9°C), Staphylococcus aureus (38.5 ± 2.2°C), and Pseudomonas aeruginosa (38.7 ± 1.9°C) exhibited a higher temperature environment. Our study provides crucial insights into the lower respiratory tract pathogenesis of heatstroke patients, identifying key pathogens and their temperature-dependent characteristics, thus providing a foundation for future empirical treatment strategies in heatstroke.